Exploring the Regional Multidimensional Poverty Pattern in Indonesia: Does Climate Matter? - Pratiwi, Ira Eka; Joshi, Niraj Prakash (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2025)
Research originality: This study develops a comprehensive regional measure of poverty using the capability approach to understand the pattern of multidimensional poverty in Indonesia. Research objectives: This study has two objectives: first, to construct and examine multidimensional poverty levels in 33 Indonesian provinces from 2010 to 2020; and second, to investigate the association between climate variables and the Multidimensional Poverty Index (MPI). Research methods: The MPI is measured through equal weighting of 20 indicators. A pooled ordinary least squares regression was used to study the relationship between the climate variables and MPI. Empirical result: The findings indicate that most provinces have experienced a decrease in poverty over the past decade. However, significant inequality persists among provinces, particularly in the eastern regions of Indonesia. Further analysis reveals that temperatures exceeding 25.25 °C may lead to an increase in the MPI, while precipitation exceeding 9.5 mm/day is associated with a decrease in the MPI. Implications: This study underscores the importance of incorporating climate change concerns, specifically increasing temperatures and unpredictable precipitation, into poverty reduction strategies and highlights the need for region-specific policies to address the multifaceted nature of poverty in Indonesia effectively. JEL Classification: I32, O10, Q54